Analisis Puisi “Aku Tidak Akan Berhenti Mencarimu” Karya Heri Isnaini dengan Pendekatan Struktural - Siti Nurhalimah; Rianti Maryana (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2023)
Literary work is a form of expression of human feelings as outlined in oral and written forms. Literary work is a language art that can be enjoyed by oneself and for everyone to enjoy. Poetry is one type of kasya satsra which is an expression of the poet's feelings which is poured using figurative words. The poem entitled "Aku Tidak Akan Berhenti MencariMu" by Heri Isnaini was chosen as research material for poetry studies using a structural approach. The Structural Approach is an approach that examines poetry based on the elements that build poetry in an objective systematic manner. This study aims to describe the physical and mental structures contained in the poem "I Will Not Stop Looking for You" by Heri Isnaini. By analyzing using a structural approach, the writer can find the meaning of a literary work. Through a structural approach, the structures studied are the physical structure and the inner structure of poetry. The method used in this research is descriptive qualitative. The qualitative description method used describes the data through words that show the meaning according to the concept. The result of this research is the discovery of all physical and mental structures in a poem by Heri Isnaini entitled "Aku Tidak Akan Berhenti MencariMu ".